On the Persistence of Racial Inequality - Lundberg, Shelly; Startz, Richard (Journal of Labor Economics, 1998)
A model of the “new growth theory” type is applied to the persistence of racial income differentials in the presence of community segregation. When community human capital affects human capital accumulation by individuals, differences between groups can persist indefinitely, even in the absence of current discrimination. Intercommunity mobility can benefit advantaged minority workers, who leave behind an impoverished ghetto. Workplace integration without community integration may not lead to equality even in the long run. We examine various policies and show that a large, temporary intervention may be successful in achieving racial equality while a smaller permanent one fails.